Design and parametric characterization of flexure bearing as automotive valve spring replacement - Mohd Razali, Hanipah; Shahin, Mansor; M. R. M., Akramin; A. R., Razali (Faculty Mechanical Engineering, UMP, 2019)
Automotive valve springs occupy substantial space in the cylinder head of an internal combustion engine and contribute to frictional loss. In this paper, the design and analyses of a flat spring concept, known as flexure bearing are presented. Flexure bearing act like a typical spring which support the shaft but only allow axial displacement, thus reduce the friction of the system. The objective of the research is to design and conduct parametric characterization of flexure bearing for valve spring replacement in a small internal combustion engine. The analyses of flexure bearing strength for different designs, materials and thicknesses were conducted using finite element method. The results show that the maximum stress values are less affected by the material type compared to the number of arms despite a significant difference in young modulus values. The strain values are limited to less than 1% for all materials when the thickness is more than 1mm. The results have provided characteristics for future selection of the flexure bearing in relation to the intended axial displacement.